The Effectiveness of Using Audio-Visual Media in Pancasila Education Learning in Elementary Schools - Zalva Arwanda; Junaidi (MIMBAR PGSD Undiksha, 2025)
Pancasila Education is a subject that plays an important role in shaping the character and personality of elementary school students. However, in practice, Pancasila learning is often perceived as uninteresting and monotonous, making it difficult for students to understand and internalize its values. This study aims to analyze the effectiveness of using audio-visual media in Pancasila Education at the elementary school level through a systematic literature review approach. The method used is a Systematic Literature Review (SLR) with the PRISMA approach, involving an analysis of 10 research articles published between 2020 and 2024. The findings indicate that the use of audio-visual media has a positive impact on the Pancasila Education learning process. This media has been proven to enhance learning outcomes, motivation, interest, student engagement, and critical thinking skills. Thus, it can be concluded that audio-visual media is effective in supporting Pancasila Education at the elementary school level. These findings have important implications for developing more relevant learning strategies tailored to students' needs and characteristics in the digital era. Therefore, it is recommended that teachers and education policymakers begin to optimally integrate audio-visual media into Pancasila Education to improve the quality of education and foster national values from an early age.